2005
DOI: 10.1097/01.mao.0000178123.35988.96
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Failures and Revision

Abstract: Management of implant failures and performance of revision surgery are becoming increasingly important in cochlear implant programs. Outcomes are generally excellent. Revision implantation is a safe and appropriate procedure that should be pursued in a timely fashion when patients experience cochlear implant failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
154
6
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(176 citation statements)
references
References 10 publications
14
154
6
2
Order By: Relevance
“…Although several reports on cochlear reimplantations have been published, only few data are available from large cohorts of patients, presenting a detailed workup on failure reasons as well as on postoperative audiologic performance. However, the existing reports have indicated that speech recognition usually remains stable after reimplantation, although it may even increase or in some cases significantly decrease [1][2][3][4][5] . Among the most commonly reported reasons for surgical revisions are failures concerning the implant housing or electrodes, software malfunction, medical reasons or poor performance despite adequate rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Although several reports on cochlear reimplantations have been published, only few data are available from large cohorts of patients, presenting a detailed workup on failure reasons as well as on postoperative audiologic performance. However, the existing reports have indicated that speech recognition usually remains stable after reimplantation, although it may even increase or in some cases significantly decrease [1][2][3][4][5] . Among the most commonly reported reasons for surgical revisions are failures concerning the implant housing or electrodes, software malfunction, medical reasons or poor performance despite adequate rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of cochlear implant failure are extrusion and malpositioning of the implant electrode, wound and flap problems, and trauma (13)(14)(15)(16). In addition, few authors have mentioned that allergy to silicon is one of the causes of cochlear implant extrusion (7-9).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies [9][10][11][12][13][14][15] have examined major complications of CI, such as reimplantations/ revision surgery hard or soft device failure. Despite the paucity of research available about repair issues associated with the external components of CI, this is an issue that deserves highlight, especially in Brazil, since such devices are dispensed by SUS, with public budget.…”
Section: Discussionmentioning
confidence: 99%